2012
DOI: 10.1155/2012/503128
|View full text |Cite
|
Sign up to set email alerts
|

PGD Synthase and PGD2in Immune Resposne

Abstract: PGD2 is formed from arachidonic acid by successive enzyme reactions: oxygenation of arachidonic acid to PGH2, a common precursor of various prostanoids, catalyzed by cyclooxygenase, and isomerization of PGH2 to PGD2 by PGD synthases (PGDSs). PGD2 can be either pro- or anti-inflammatory depending on disease process and etiology. The anti-inflammatory and immunomodulatory attributes of PGDS/PGD2 provide opportunities for development of novel therapeutic approaches for resistant infections and refractory inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 63 publications
3
77
0
1
Order By: Relevance
“…However, the immunostimulatory mechanisms of these lipid mediators are not well defined (45). Since 15d-PGJ 2 is a PPAR␥ ligand, we investigated whether these effects were mediated by PPAR␥ and whether PPAR␥ agonists enhance bacterial phagocytosis and killing.…”
Section: Ppar␥ Agonists Enhanced Phagocytosis and Bacterial Clearancementioning
confidence: 99%
“…However, the immunostimulatory mechanisms of these lipid mediators are not well defined (45). Since 15d-PGJ 2 is a PPAR␥ ligand, we investigated whether these effects were mediated by PPAR␥ and whether PPAR␥ agonists enhance bacterial phagocytosis and killing.…”
Section: Ppar␥ Agonists Enhanced Phagocytosis and Bacterial Clearancementioning
confidence: 99%
“…We and others have shown that activation of cyclooxygenase-2 (COX-2) and production of lipid mediators play a pivotal immunomodulatory role in fungal, viral, and bacterial infections (21)(22)(23)(24)(25). In particular, PGE 2 has immunosuppressive effects and impairs bacterial clearance (22,23,(26)(27)(28)(29), whereas PGD 2 has been shown to have immunostimulatory effects (30,31).…”
mentioning
confidence: 99%
“…Several subtypes of PGs with distinct activities have been described, including PGE 2 , PGI 2, and PGD 2 (Harris et al, 2002). Among them, PGD 2 has been characterized as eosinophil chemo attractant (Monneret et al, 2001) and anti-inflammatory agent (Joo et al, 2007;Joo and Sadikot, 2012;Murata et al, 2013). Intratracheal administration of PGD 2 has been shown to decrease the bacterial load in the lungs of Pseudomonas aeruginosa-infected mice (Joo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%